What is a disaster? – Approaches to and examination of disaster theory (Academic Journal of Internal Affairs, 2020)
The concept of disaster is difficult to define and has different meanings depending on the context. Throughout the brief history of disaster science, a number of approaches were applied to this basic term: according to the historical, political, professional, and cultural context, and to its research subject, the ’disaster’ was defined in several ways. That is why a clear concept is difficult to establish. This paper is a summary that investigates the approach and risk interpretation of various schools of disaster theory, including only the most widely used classical, social, scientific, anthropological and political approaches. In addition, it summarizes the concepts used in professional documents with problem-oriented approach. The author intends to provide a point of reference for the Hungarian academic sphere in disaster science, for university students and disaster management professionals.
Keywords: disaster theory; disaster science; disaster management; police science